Mechanical and Thermal Sensory Testing in Normal Chondrodystrophoid Dogs and Dogs with Spinal Cord Injury caused by Thoracolumbar Intervertebral Disc Herniations. (5th March 2016) - Gorney, A.M.; Blau, S.R.; Dohse, C.S.; Griffith, E.H.; Williams, K.D.; Lim, J.‐H.; Knazovicky, D.; Lascelles, B.D.X.; Olby, N.J.
Abstract : Background: Intervertebral disc herniation is a common cause of spinal cord injury (SCI) causing paralysis and sensory loss. Little quantitative information is available on the loss and recovery of sensation in dogs with SCI. Objectives: To determine whether quantitative sensory testing (QST) can be used to establish thermal and mechanical sensory thresholds in chrondrodystrophoid dogs and compare thresholds among normal dogs and dogs with different grades of SCI. Animals: Thirty‐three client‐owned chondrodystrophoid dogs: 15 normal and 18 SCI dogs. Methods: Thermal testing was performed by placing a hot (49°C) and cold (5°C) probe on the dorsal metatarsus and mechanical thresholds were tested using calibrated forceps to apply force to the lateral digit. Stimuli were applied until acknowledged, and response rate, latency, and force applied to response were recorded. Test‐retest repeatability was determined by calculating intraclass correlation coefficients. Response rates were compared using logistic regression and thresholds were compared using Kaplan–Meier Survival curves. Results: Testing was feasible with moderate repeatability. Thresholds and response rates were significantly different between normal and SCI dogs for all modalities ( P < .001). When dogs were grouped by their clinical grade, each grade was significantly different from normal dogs, and cold stimuli differentiated among all grades. Conclusion and clinical importance: Sensory thresholds can be measured reliably in chondrodystrophoid dogs and are altered by SCI. The differences in sensation among neurologic grades indicate that these techniques can be used to further characterize recovery of SCI dogs.